A global phylogeny of Stegnogramma ferns (Thelypteridaceae): generic and sectional revision, historical biogeography and evolution of leaf architecture. (28th July 2019) - Kuo, Li‐Yaung; Chang, Yi‐Hang; Huang, Yu‐Hsuan; Testo, Weston; Ebihara, Atsushi; Rouhan, Germinal; Quintanilla, Luis G.; Watkins, James E.; Huang, Yao‐Moan; Li, Fay‐Wei
Abstract: The thelypteroid fern genus Stegnogramma s.l. contains around 18–35 species and has a global, cross‐continental distribution ranging from tropical to temperate regions. Several genera and infrageneric sections have been recognized previously in Stegnogramma s.l., but their phylogenetic relationships are still unclear. In this study, we present a global phylogeny of Stegnogramma s.l. with the most comprehensive sampling to date and aim to pinpoint the phylogenetic positions of biogeographically and taxonomically important taxa. Based on the reconstructed historical biogeography and character evolution, we propose a new (infra)generic classification and discuss the diversification of Stegnogramma s.l. in a biogeographical context. New names or combinations are made for 12 (infra)species, including transferring the monotypic species of Craspedosorus to Leptogramma . Finally, we discuss a possible link between leaf architecture and ecological adaptation, and hypothesize that the increase in leaf dissection and free‐vein proportion is an adaptive feature to cool climates in Stegnogramma s.l.